Arterial stiffness, sex, and age difference on hypertensive response to supine bicycle exercise. Issue 12 (25th October 2017) - Chung, Hyemoon; Kim, Jong‐Youn; Lee, Byoung Kwon; Min, Pil‐Ki; Yoon, Young Won; Hong, Bum‐Kee; Rim, Se‐Joong; Kwon, Hyuck Moon; Choi, Eui‐Young
Abstract : Contributors to a hypertensive response to exercise (HTR) according to sex and age have not been fully evaluated. The authors analyzed a database of supine bicycle exercise stress echocardiography findings. HTR was defined as peak systolic blood pressure ≥210 mmHg for men and ≥190 mmHg for women during exercise. A total of 797 patients (306 [38%] women) were analyzed, with a mean age of 64 ± 10 years. Female sex, hypertension; higher left ventricular ejection fraction, effective arterial elastance, and pulse wave velocity; and lower total arterial compliance were significantly related to HTR. Patients with HTR had higher relative wall thickness, ratio of early diastolic mitral inflow and annular velocity, and diastolic elastance (all P ≤ .05). In multivariable analysis, indices of arterial stiffness such as pulse wave velocity, arterial elastance, total arterial compliance, and systemic vascular resistance were more strongly related in women, while in men, index of sympathetic activation was additionally related to HTR (all P ≤ .05). Female sex and lower total arterial compliance in older patients (≥65 years) and higher systemic vascular resistance and left ventricular relative wall thickness in younger patients were more strongly related to HTR. In conclusion, HTR was related to arterial stiffness, sympathetic activation, and diastolic dysfunction; however, the associations were different according to sex and age, which might guide individualized therapy.